Multi-Parameter Vibration Analysis for Bearing Fault Detection at Low Speeds Using Standard Accelerometers with Stud and Magnetic Mounting - Noviandy, Noviandy; Rusli, Meifal (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
Detecting bearing defects at low rotational speeds remains a major challenge due to weak impulsive responses and dominant low-frequency components. This study evaluated the feasibility of using a standard industrial accelerometer (1 µA/ms², equivalent to 100 mV/g) for detecting outer race defects in bearings operating at 100–300 RPM. Experiments were conducted under both baseline and defected conditions using two mounting configurations: stud and magnetic. Vibration responses were analysed through overall values (velocity, acceleration, and shock pulse), spectral analysis, enveloped signals, and time waveform comparisons. Results show that standard accelerometers can effectively detect bearing defect signatures in low-speed machines (100–300 RPM), with diagnostic performance strongly influenced by the sensor mounting method. At 100 RPM, magnetic mounting occasionally recorded higher acceleration readings (?30%) due to uneven impulsive energy distribution and low-speed dynamic instability. At higher speeds (200–300 RPM), stud mounting produced stronger and more stable responses, with amplitudes about 2–8% higher than magnetic mounting, confirming its superior coupling rigidity. Spectral analysis alone was limited by broadband noise, while time waveform and envelope analyses revealed clearer defect-related impacts, particularly at 1× RPM and 2× BPFO. Overall, stud-mounted sensors demonstrated more consistent and reliable performance, validating their suitability for accurate and practical low-speed vibration monitoring.